Withdrawing and witholding medical treatment: a comparative study between the Malaysian, English and Islamic law - Jahn Kassim, Puteri Nemie; Omipidan, Bashiru Adeniyi (World Association of Medical Law, 2010)
The permissibility and lawfulness of withdrawing and withholding medical treatment has attracted considerable debates and criticisms, as the legal issues are drawn into entering the slippery slope of euthanasia. Proponents of “sanctity of life” views that withdrawing and withholding medical treatment with knowledge that death would result is still within the sphere of euthanasia, whereas proponents of “quality of life” argue that it is not, as death is not intended. Their arguments maintain that for patients who are totally dependant on machines to ensure the work of some bodily functions, living may amount to little more than survival as dying is prolonged. Furthermore, the prolonging of life of the dying patient has profound implications on patients themselves, their relatives, dependants and medical providers. Thus, withdrawing and withholding medical treatment would not only respect a patient's right to self-determination, by allowing them to the in their underlying condition, but will ensure that medical providers are able to concentrate on more worthwhile treatments. This paper discusses the intractable difficulties with the moral distinction between withholding and withdrawing treatment and euthanasia, as well as makes a comparative study between the present state of law in Malaysia and England on this issue. The paper further highlights the differences between civil law and Islamic law in this controversial area.